The triumph of broken promises the end of the Cold War and the rise of neoliberalism - Bartel, Fritz (Harvard University Press, 2022)
"Communist and capitalist states alike were scarred by the economic shocks of the 1970s. Why did only communist governments fall in their wake? Fritz Bartel argues that Western democracies were insulated by neoliberalism. While austerity was fatal to the legitimacy of communism, democratic politicians could win votes by pushing market discipline"--